Quiet influence : the introvert's guide to making a difference - Kahnweiler, Jennifer B. (BK life book., 2013)
Introverts Do It Quietly Introverts may feel powerless in a world where extroverts seem to rule, but there?s more than one way to have some sway. Jennifer Kahnweiler proves introverts can be highly effective influencers when, instead of trying to act like extroverts, they use their natural strengths to make a difference. Kahnweiler identifies six unique strengths of introverts and includes a Quiet Influence Quotient (QIQ) quiz to measure how well you?re using these six strengths now. Then, through questions, tools, exercises, and powerful real-world examples, you will increase your mastery of these strengths. This extraordinary book shows that you don't have to raise your volume to have a voice.? Susan Cain, author of the New York Times Bestseller Quiet?Jennifer Kahnweiler shows you how the masters of the art of quiet are able to get more done, be more creative, and sustain more energy than those who often live and work at a frantic, out-loud, always-on pace. The lessons in Quiet Influence will increase your capacity to have a profound effect on the actions and thoughts of others.??Jim Kouzes, coauthor of The Leadership Challenge and Dean?s Executive Fellow of Leadership, Leavey School of Business, Santa Clara University?Quiet Influence is a great resource for introverts who want to learn how to use their strengths to maximize their effectiveness in the workplace. But wait?it?s also a wonderful handbook for extroverts (like me) who want to understand more about what makes their less-gregarious friends and colleagues tick.??Ken Blanchard, coauthor of The One Minute Manager and Great Leaders Grow?Jennifer Kahnweiler shows millions of introverts how to harness the strengths they already have. It is the must-have guide to greater insight and impact that we?ve been waiting for.??Dudley White, Senior Vice President, Professional Services, Equifax.